The interplay between cognitive impairment and mental health in women with PCOS: a systematic review - Agarwal, Tanika; Singh, Satvir (International Journal of Research in Medical Sciences, 2025)
Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders affecting women of reproductive age. While its physical symptoms such as irregular menstruation, acne and infertility receive considerable attention, the cognitive and psychological burdens associated with PCOS often go unnoticed. This study conducted a systematic narrative review to synthesize the existing literature on the cognitive and mental health implications of PCOS. A comprehensive search across PubMed, Scopus and Web of Science was performed for studies published between 2015 and 2025. Using PRISMA guidelines, we identified 52 initial records, from which 12 high-quality studies were included. Both subjective tools (like psychological inventories) and objective assessments (e.g., MoCA, EEG, ERP) were analyzed to understand the interplay between PCOS and cognitive or emotional well-being. Findings revealed consistent patterns of cognitive impairments in attention, memory and executive functioning among women with PCOS. Neurophysiological data, such as reduced P300 amplitudes and abnormal EEG rhythms, supported these clinical symptoms. Simultaneously, a high prevalence of anxiety (up to 42%) and depression (around 37%) was reported, often aggravated by body image issues, infertility and sociocultural stigma. Notably, cognitive decline and psychological distress appeared interlinked, forming a feedback loop that intensifies suffering over time. A person’s emotional and mental well-being are intricately related to polycystic ovary syndrome (PCOS). A multidisciplinary strategy is urgently needed to treat polycystic ovary syndrome (PCOS), which includes cognitive screening and psychological assistance as part of standard treatment.